Eliminating on the divergences o f the photon self - energy diagram in (2+1) dimensional quantum electrodynamics - Han, Nguyen Suan; Xuan, Nguyen Nhu (VNU Journal of Science: Mathematics - Physics, 2007)
The divergence o f the photon self-energy diagram in spinor quantum electrodynamics in (2 + 1 ) dimensional space time- (QEDs) is studied by the Pauli-Villars regularization and dimensional regularization. Results obtained by two diíTerent methods are coincided i f the gauge invariant o f theory is considered carefully step by step in these calculations.